Publishing Privileges the Published: An Analysis of Gender, Class, and Race in the Hymnological Feedback Loop - Katie Graber; Anneli Loepp Thiessen (Religions, 2023)
Hymnal curation processes have for centuries maintained restrictive feedback loops: material that has been published elsewhere continues to be published, and new material—particularly when it offers something unique—is evaluated against the criteria of what has gone before. This results in hymnals that tend to over-represent the work of white male contributors from a Euro–American perspective and limits the amount of material by women, people of color, and contributors from around the world. Since the mid-to-late twentieth century, when some denominations have sought to diversify their worship music collections, change has come slowly. Contemporary hymnody and contemporary worship music are predominantly written by men, and additions of global song have relied on a narrow swath of scholars and publications. To understand some of the power imbalances embedded in church music publishing, we use Voices Together, the 2020 Mennonite hymnal for which we were committee members, as a case study. We explore how this new collection came to include only about 45 newly published songs out of the total of 749 songs, and we analyze statistics related to gender and global song. An intersectional approach allows us to examine how musical actors are marginalized in multiple ways, considering prejudice against class, race, and gender. Understanding how current collections are informed by previously published collections, and consequently how the demographics of contributors have shifted over time, explains how publishing privileges the published and offers insight needed to begin to rectify this problem.